Reduced partition function ratios of iron and oxygen in goethite. (15th February 2015) - Blanchard, M.; Dauphas, N.; Hu, M.Y.; Roskosz, M.; Alp, E.E.; Golden, D.C.; Sio, C.K.; Tissot, F.L.H.; Zhao, J.; Gao, L.; Morris, R.V.; Fornace, M.; et al.
Abstract: First-principles calculations based on the density functional theory (DFT) with or without the addition of a Hubbard U correction, are performed on goethite in order to determine the iron and oxygen reduced partition function ratios (β-factors). The calculated iron phonon density of states (pDOS), force constant and β-factor are compared with reevaluated experimental β-factors obtained from Nuclear Resonant Inelastic X-ray Scattering (NRIXS) measurements. The reappraisal of old experimental data is motivated by the erroneous previous interpretation of the low- and high-energy ends of the NRIXS spectrum of goethite and jarosite samples (Dauphas et al., 2012). Here the NRIXS data are analyzed using the SciPhon software that corrects for non-constant baseline. New NRIXS measurements also demonstrate the reproducibility of the results. Unlike for hematite and pyrite, a significant discrepancy remains between DFT, NRIXS and the existing Mössbauer-derived data. Calculations suggest a slight overestimation of the NRIXS signal possibly related to the baseline definition. The intrinsic features of the samples studied by NRIXS and Mössbauer spectroscopy may also contribute to the discrepancy (e.g., internal structural and/or chemical defects, microstructure, surface contribution). As for oxygen, DFT results indicate that goethite and hematite have similar β-factors, which suggests almost no fractionation between the two minerals at equilibrium.